The Development and oprimization of process for the expression of sialylated recombinant human therapeutic glycoprotein in insect cell-baculovirus system. - Abd. Aziz, Azila; Abd. Rahman, Badarulhisam; Idris, Ani (Faculty of Chemical and Natural Resource Engineering, 2006)
The objectives of this research were to determine the optimal parameters (culture conditions, transferases and sugar nucleotides content) for the expression of complete recombinant human glycoprotein and develop an optimal processing condition for the production of human like glycoprotein in an artificial system by the manipulation of metabolic engineering and process engineering approach. In the early part of the study, fundamental works were carried out to optimize Spodoptera frugiperda (Sf-9) cells growth and mock infection. Serum concentration, different type of media, cell subculturing condition, initial cell density and spent medium carry over had been found to significantly influence the growth kinetics of Sf-9 cells. The optimized parameters were then used to evaluate the expression of recombinant hTf and 1,4-GalT in Sf-9 cells. Time course expression profiles of rhTf at various multiplicities of infection (MOI), seeding densities (SD), times of infection (TOI), and harvest times (HT) were studied. Screening experiments were conducted to identify the medium components in Sf900-II SFM and the recombinant baculovirus stock that resulted in improved production of rhTf. Finally, Response Surface Methodology (RSM) was employed to hunt for optimum medium composition. The results showed that the optimum HT for rhTf was between 24 to 72 hours post infection, at SD of 1.6 x 10 6 viable cells/ml, TOI of day 2 post seeding, and MOI of 5 pfu/cell. Glucose and glutamine were found to have the most positive effect on rhTf production with more than 95% significance. In addition to that, the best recombinant baculovirus stock was identified at 98.7% purity. With the optimized parameters, rhTf production had increased three-fold from 19.89g/ml to 65.12g/ml. Subsequently, native UDP-Gal levels at normal and upon baculovirus infection produced in Sf-9 cells were monitored using Reverse Phase High iv Performance Liquid Chromatography. UDP-Gal concentration was discovered to decrease gradually once infected with the recombinant baculovirus. Finally, baculovirus coinfection study was carried out to evaluate the recombinant glycoprotein quality. However, lectin binding analysis using Ricinus communis agglutinin-I, revealed that co-expression between rhTf and -1,4GalT (in vivo) did not show encouraging result due to the reduction of UDP-Gal upon baculovirus infection. This finding suggested that the introduction of -1,4GalT alone was not sufficient for successful galactosylation. However, another strategy was used to overcome the problem. Commercial GalT and UDP-Gal were introduced artificially to the rhTf after it was secreted from cell culture. It was found that the in vitro strategy promoted better N-glycan quality in insect cells. Last stage of the research was based on rhTf purification, to get a pure rhTf with improved recovery. Steps of purification were hydrophobic chromatography, dialysis and ion exchange chromatography. Elution strategy, flowrate and rhTf loading capacity of phenyl sepharose 6 fast flow were optimized. Batch purification in reduced sized was used to select suitable anion exchange matrix, pH and concentration of equilibration buffer. 74.6% of rhTf was recovered from phenyl sepharose, 86.8% recovered after dialysis, and 52.5% recovered from Q-sepharose and the overall recovery of pure rhTf was 34%.